2013
DOI: 10.1017/s0266467412000727
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of tree species along a gallery forest–savanna gradient: patterns, overlaps and ecological thresholds

Abstract: Abstract:Savannas intermingled with gallery forests are dynamic habitats typical in Africa. This study aims to determine if differences in species traits lead to non-overlapping distribution of gallery-forest and savanna species and abrupt transition between gallery forest and savanna. Tree species densities were measured in 375 plots of 1500 m2 covering a total sample area of 56.25 ha along forty 3-km transects located at right angles to a riverbed with gallery forest into surrounding savanna. Location, veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 50 publications
(101 reference statements)
1
19
0
1
Order By: Relevance
“…), we observed no gallery forest effect (compare Azihou et al. ). Lithraea caustica seemed better able to retain soil moisture under its own canopy up to a week after rain, which might favor the germination of seeds requiring higher soil moisture to grow deeper root systems, or might be advantageous in particularly dry areas such as rain shadows or the northern limit of espinal distribution, if the increased shade is tolerated (compare Badano et al.…”
Section: Discussionsupporting
confidence: 49%
“…), we observed no gallery forest effect (compare Azihou et al. ). Lithraea caustica seemed better able to retain soil moisture under its own canopy up to a week after rain, which might favor the germination of seeds requiring higher soil moisture to grow deeper root systems, or might be advantageous in particularly dry areas such as rain shadows or the northern limit of espinal distribution, if the increased shade is tolerated (compare Badano et al.…”
Section: Discussionsupporting
confidence: 49%
“…Fire has long been proposed as a key limit on the success of tree establishment in savannas (Scholes and Archer 1997, Bond 2008, Staver et al 2011, Murphy and Bowman 2012, where the vulnerability of tree seedlings to fire is expected to play a large role in maintaining diversity and codominance of trees and grasses in these ecosystems through nonequilibrium, demographic-bottleneck models (Higgins et al 2000, Sankaran et al 2004. Previous work in our study region has documented low seedling to sapling transitions in many gallery forest species, including K. senegalensis (Azihou et al 2013b), and has suggested that fire may play a key role in restricting these species to gallery forest in dry regions (Azihou et al 2013a). Consistent with these predictions, the extent of burning was a component of the final model for all response variables tested here except sapling survival, underscoring the importance of fire in driving seedling dynamics in this mesic savanna system.…”
Section: Facilitation Fire and Savanna Dynamicsmentioning
confidence: 79%
“…The fact that the riparian woody density is lower in FA would result in much drier forests due to the increase in the surface exposure of the riparian area for soil moisture loss. This can increase the vulnerability and frequency of the RF to savanna fires (Azihou et al, 2013). Such fires can break the resilience of the riparian ecosystem to intensify climate change impacts to such a degree that species physiological tolerances can be exceeded and the rates of biophysical forest processes altered.…”
Section: Changes In Riparian Woody Species Density Basal Area and Simentioning
confidence: 99%
“…However, certain outcomes of climate change can be mitigated by maintaining intact riparian landscapes-including retaining soil moisture, regulation of localized fire, and provision of refuge and dispersal corridors for fauna (Goetze et al, 2006;Azihou et al, 2013). Ecologically, riparian forests (RF) are important as they protect farmlands from flooding, drying and sedimentation (Gray et al, 2014).…”
Section: Introductionmentioning
confidence: 99%